2019
DOI: 10.1109/tsg.2017.2785040
|View full text |Cite
|
Sign up to set email alerts
|

Combined Stochastic Optimization of Frequency Control and Self-Consumption With a Battery

Abstract: Optimally combining frequency control with selfconsumption can increase revenues from battery storage systems installed behind-the-meter. This work presents an optimized control strategy that allows a battery to be used simultaneously for self-consumption and primary frequency control. Therein, it addresses two stochastic problems: the delivery of primary frequency control with a battery and the use of the battery for self-consumption.We propose a linear recharging policy to regulate the state of charge of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…which is limited by the maximum power |P grid t | ≤ P BESS max of the BESS. This controller can be seen as an extension of the rule-based controllers proposed in [4], [5], [6], [13], [38] and [39], and as a special case of the ones in [40], [41] and [42]. Figure 7 shows an example of the grid power P grid t of a battery delivering r = 1 MW of FCR capacity, according to (7).…”
Section: Fcr Controllermentioning
confidence: 99%
“…which is limited by the maximum power |P grid t | ≤ P BESS max of the BESS. This controller can be seen as an extension of the rule-based controllers proposed in [4], [5], [6], [13], [38] and [39], and as a special case of the ones in [40], [41] and [42]. Figure 7 shows an example of the grid power P grid t of a battery delivering r = 1 MW of FCR capacity, according to (7).…”
Section: Fcr Controllermentioning
confidence: 99%
“…In our previous work [21], we showed that this approximation does not lead to violations of the constraints when η c , η d < 1.…”
Section: A Frequency Control Frameworkmentioning
confidence: 75%
“…This work fills this gap by presenting an operational control framework that enables a BESS to successfully combine peak shaving with frequency control services. The presented method extends our previous work on frequency control with BESSs [21], by adding the peak shaving objective using dynamic programming and a customised stochastic optimisation objective. The main contributions of this paper are:…”
Section: Related Literaturementioning
confidence: 90%
See 1 more Smart Citation
“…In the Regional Group Nordic area, the implementation of this service is called Frequency-Normal Operation Reserve (FNR). Various studies have shown the profitability of such services for battery systems and EVs, as well as the power system [1,2,3].…”
Section: Introductionmentioning
confidence: 99%